Strategic planning as a competitive differential: A case study of the Sealed Sources Production Laboratory - VIEIRA, IMARIO (2018)
Strategic planning has always been and continues to be one of the most important management tools for decision making. Amidst the uncertainties of the 21st century, public, private and third sector organizations are steadily struggling to improve their strategic plans by using more effective results management tools such as BSC-Balanced Scorecard. Nuclear research institutes and research centers around the world have been using more and more these types of tools in their strategic planning and management. The objective of this article was to recommend the use the BSC as a strategic tool for decision making for the Sealed Sources Production Laboratory located in the Radiation Technology Center, at Nuclear and Energy Research Institute (IPEN/CNEN-SP), in S??o Paulo, Brazil. The methodology used in this academic article was a case study, which considered the object of the study, the Sealed Sources Production Laboratory, from January 2014 to August 2016. Among the main results obtained with this study can be cited: the improvement of the information flow, the visualization and proposition to change the periodicity of analysis of the results, among others. In view of the expected results, it was possible to conclude that this study may be of value to the Sealed Sources Production Laboratory for Industrial Radiography and Industrial Process Control and also to other research centers, as it will allow and contribute with an additional management support tool.